AN ANALYSIS OF TEACHERS’ PERSPECTIVE ON STUDENTS’ SPEAKING SKILL PROBLEMS AT TENTH GRADE STUDENTS OF SMK DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2019/2020 - Ebidona, Yuliana; Yuniari, Ni Made (Widya Accarya, 2020)
Abstract This research aimed to know the students' problems in speaking skills at the tenth-grade students of SMK Dwijendra Denpasar Based on Teachers’ perspective, this research was a qualitative case study. The subjects of this research were two English Language teachers of SMK Dwijendra Denpasar. They were data collected through some instrument namely observation, an interview guide, recording, analysis documents, and interviewing. The findings showed that they were three difficulties faced by students when learning English was the level of mastery of vocabulary students have very less and Grammatical Errors in speaking, students experience difficulties and errors, especially in arranging sentences correctly. The strategies used by teachers to overcome students' problems in their ability to speak English were through strategies 1) small group discussions 2) Reading, 3) Practicing Dialogue and Retelling, 4) Translation According to the subject, 5) staring at the dictionary, 6) taking notes, 7) Provides opportunities for students to use vocabulary in real life contexts. The efforts made by teachers to make teaching and learning activities in English classes more interesting were1) by collaborating learning with games related to teaching materials. 2) play a word game. 3) provides opportunities for students to use vocabulary in real life contexts. Keywords: Teacher's perspective, speaking skills, Students’ problems Abstrak Penelitian ini bertujuan untuk mengetahui permasalahan siswa dalam keterampilan berbicara pada siswa kelas X SMK Dwijendra Denpasar bersadarkan perspektif Guru. Penelitian ini merupakan studi kasus kualitatif. Subjek penelitian ini adalah dua orang guru Bahasa Inggris SMK Dwijendra Denpasar. Pengumpulan data dilakukan melalui beberapa instrumen yaitu observasi, pedoman wawancara, pencatatan, analisis dokumen, dan wawancara. Hasil penelitian menunjukkan bahwa ada tiga kesulitan yang dihadapi siswa ketika belajar bahasa Inggris dimana tingkat penguasaan kosakata siswa sangat kurang dan Grammatical Errors dalam berbicara, siswa mengalami kesulitan dan kesalahan terutama dalam menyusun kalimat dengan benar. Strategi yang digunakan guru untuk mengatasi masalah siswa dalam kemampuan berbahasa Inggris adalah melalui strategi 1) Diskusi Kelompok Kecil 2) Membaca, 3) Berlatih Dialog dan Menceritakan Kembali, 4) Penerjemahan Sesuai Mata Pelajaran, 5) Menatap Kamus, 6) mencatat, 7) Memberikan kesempatan kepada siswa untuk menggunakan kosakata dalam konteks kehidupan nyata. Upaya yang dilakukan oleh guru untuk membuat kegiatan belajar mengajar di kelas bahasa Inggris lebih menarik adalah 1) dengan mengkolaborasikan pembelajaran dengan permainan yang berkaitan dengan bahan ajar. 2) Mainkan permainan kata. 3) memberikan kesempatan kepada siswa untuk menggunakan kosakata dalam konteks kehidupan nyata. Kata kunci Perspektif Guru, Keterampilan Berbicara, Masalah Siswa